Metaphoric Elaboration in a Narrative-Conversational Intervention for Drug Abuse Treatment - Gracia-Gutiérrez de Velasco, Sara Elisa; Díaz-Negrete, David Bruno; Fernández-Cáceres, Carmen (Revista de Psicología, 2015)
This paper describes the elaborative process drawn from the implementation of a brief narrative-conversational intervention, aimed at reinforcing treatment and social reintegration of people with drug abuse problems. The intervention comprised three sessions focused on a dialogical reconstruction of the experience in treatment and expectations about social reintegration, by means of a narrative exercise based on the metaphor of treatment as a journey. A sample of 10 participants was recruited from two treatment units in Mexico City. Active listening led to a greater cognitive-affective integration of treatment experience, as well as to clearing up expectations, fears and desires caused by the upcoming end of treatment. An ample metaphorical production was observed, which was linked to new ways of signifying experience, a wide expression of affections, and a clearer picture of the future.